Growth of magnetic metals on carbon microspheres with synergetic dissipation abilities to broaden microwave absorption. (30th April 2022) - Zhao, Biao; Li, Yang; Zeng, Qingwen; Fan, Bingbing; Wang, Lei; Zhang, Rui; Che, Renchao
Highlights: Facile electrostatic assembly approach for preparation of core-shell C/magnetic metal composite microspheres. Excellent microwave absorption performance including a maximum reflection loss value of −54.1 dB and a broad effective absorption bandwidth of 6.7 GHz. Profound magnetic coupling effect and magnetic-dielectric synergy mechanism for enhancing microwave absorption performance. Abstract: Microwave absorption (MA) materials have been captured extensive attentions due to the serious electromagnetic (EM) pollution. Numerous interests focus on the MA performances of core-shell structural composites with magnetic constituents as cores and dielectric constituents as shells, which inevitably suppressed the magnetic coupling causing the decrease of magnetic loss to some extent. Herein, the core-shell structural carbon (C) microsphere/magnetic metal composites were fabricated through the combination of an electrostatic assembly approach and subsequent in-situ reduction reaction. The complex permittivity and permeability of core-shell C@magnetic metal composite system can be effective adjusted by the constituent and microstructure of shells. Thanks to the distinct magnetic coupling from the subtle designed structures and the promotion of the magnetic-dielectric synergy, the C@magnetic metal composite exhibited enhanced MA properties. The optimal reflection loss (RL) of C@Ni composite was -54.1 dB with a thickness of 3.4 mm, meanwhile the effective absorbing band could reach over 5.5 GHz at only a 1.8 mm thickness. Broad absorption bandwidth with RL below -10 dB could achieve 6.0 GHz and 6.7 GHz for C@Co and C@NiCo composites with a thin 2.1 mm thickness, respectively. Our exciting findings might lead a guide on the novel structure design for the functional core-shell structural composites used for microwave absorption. Graphical Abstract: Graphical Abstract Image, graphical abstract .